2011
DOI: 10.1111/j.1399-0039.2011.01757.x
|View full text |Cite
|
Sign up to set email alerts
|

Mothers without HLA antibodies before transplantation have a low risk of alloimmunization post‐transplantation

Abstract: Human leukocyte antigen antibodies (HLA Abs) are associated with poor renal graft outcome. We selected 134 first kidney transplant recipients without HLA Ab (LABScreen® Luminex) before transplantation despite previous allogeneic exposure whether through blood transfusion (BT) and/or pregnancy (PR). We screened these patients for HLA Ab post-transplantation (yearly) and determined the risk of HLA Ab and donor-specific antibody (DSA) appearance according to BT/PR in a univariate and a multivariate model. Among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Similar conclusions were reached with a mathematical model based on a database of thousands of transfusion recipients in diverse patient populations . Data from the transplantation setting suggest that women who are not alloimmunized during pregnancy are less likely to develop donor‐specific antibodies after transplantation …”
supporting
confidence: 62%
See 1 more Smart Citation
“…Similar conclusions were reached with a mathematical model based on a database of thousands of transfusion recipients in diverse patient populations . Data from the transplantation setting suggest that women who are not alloimmunized during pregnancy are less likely to develop donor‐specific antibodies after transplantation …”
supporting
confidence: 62%
“…23,25,26 Data from the transplantation setting suggest that women who are not alloimmunized during pregnancy are less likely to develop donor-specific antibodies after transplantation. 27 Recent technologic developments (i.e., highthroughput, genomewide single-nucleotide polymorphism [SNP] genotyping using commercial arrays) enable the comprehensive search for genetic variation associated with differing risks of alloimmunization. 28 Here we report the results of a genomewide association study (GWAS) including 752 alloantibody-positive and 753 alloantibody-negative, previously pregnant female blood donors who had been enrolled in the Leukocyte Antibody Prevalence Study (LAPS).…”
Section: Resultsmentioning
confidence: 99%
“…A different cutoff value to discriminate positive and negative results may explain this, because the Dutch blood donor cohort also revealed a higher proportion of HLA antibodies in nontransfused males (9% vs. 1%, respectively) 11 . Densmore 8 and colleagues reported that HLA antibodies declined after 5 years after delivery using a functional test as the CDC, while Powers and coworkers 10 and Gatault and coworkers 34 reported longer persistence of HLA antibodies using more sensitive Luminex techniques 35 . Although in comparative assays, Luminex‐based techniques are most sensitive compared to ELISA, FlowPRA, and CDC, the cutoff is not equivocal 18 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more sensitive and specific methods are used to detect HLA antibodies such as ELISA, flow cytometry, and Luminex technology. 24 …”
Section: Importance Of the Anti-hla Antibodies In Transplantationmentioning
confidence: 99%
“…23 The methods used for HLA antibody detection has been developed in the last 10 years. 24 It is known that HLA antibodies are IgG type. Thus the methods used for the anti-HLA antibody detection target IgG subunits.…”
Section: Importance Of the Anti-hla Antibodies In Transplantationmentioning
confidence: 99%